QTc prolongation in hospitalized pediatric patients receiving methadone - Schwinghammer, Amy J. (Pediatr Crit Care Med, 2018)
OBJECTIVE: Methadone is often used in pediatric patients to prevent or treat opioid withdrawal after prolonged sedation. Prolonged QTc is an important adverse effect of methadone because it can progress to torsades de pointes (TdP), a potentially fatal dysrhythmia. The incidence of QTc prolongation and contributing risk factors are not well-defined in hospitalized pediatric patients receiving methadone. The study purpose was to identify the frequency and risk factors of QTc prolongation in hospitalized pediatric patients receiving methadone. DESIGN: Retrospective cohort study. SETTING: Tertiary academic pediatric hospital, University of California Davis Children’s Hospital, Sacramento, California. PATIENTS: Cohort of 89 pediatric patients (birth to 18 years) who received at least one dose of methadone while hospitalized. INTERVENTIONS: Retrospective data over 7.5 years were obtained from the electronic health record. MEASUREMENTS AND MAIN RESULTS: From the cohort, 45 patients (50.6%) had documented QTc prolongation (≥450 ms) during the study period. No episodes of TdP were identified. In univariate analyses, higher maximum methadone doses were associated with a prolonged QTc (0.98 vs 0.59 mg/kg/day, OR 2.56, 1.15 – 5.70). QTc prolongation occurred more frequently in patients with cardiac disease (63% vs 41%, p = 0.10). No factors were statistically significant in the multivariate analysis. CONCLUSIONS: In hospitalized pediatric patients receiving methadone, QTc prolongation was common but no episodes of TdP were documented. Risk factors that have been identified in adults were not associated with prolongation in our study population.